Epidemiological features and disease-related concerns of a large cohort of Italian patients with active Crohn's disease. Issue 6 (June 2019) - Armuzzi, Alessandro; Riegler, Gabriele; Furfaro, Federica; Baldoni, Monia; Costa, Francesco; Fortuna, Manuela; Iaquinto, Gaetano; Paese, Pietro; Papi, Claudio; Bossa, Fabrizio; Tontini, Gian Eugenio; Di Fino, Sara; et al.
Abstract: Background-Aims: The SOLE study was conducted on a large cohort of Italian patients with moderate-severe Crohn's disease (CD) to assess epidemiological and disease characteristics and their correlation with disease-related worries, treatment satisfaction and adherence, workability. Methods: The following tools were used over 12 months to assess: disease-related worries: Rating Form of Inflammatory Bowel Disease Patient Concerns, impact on workability: Work Productivity and Activity Impairment-CD, satisfaction: Treatment Satisfaction Questionnaire for Medication, adherence: Medication Adherence Rating Scale. Results were correlated with demographic and clinical variables with linear regression models. Results: 552 patients with active CD (51% men) were recruited. Higher worries were having an ostomy bag and undergoing surgery. Variables associated with a higher RFIPC score included female sex, higher disease activity, lower treatment adherence (p < 0.001), previous surgical treatments (p = 0.003). 60% of patients claimed difficulties with activities of daily living. Lower VAS scores were reported by patients with disease duration >6years; treatment satisfaction/adherence was higher with anti-TNF-α treatment. Decreased hospitalizations during follow-up and improved workability/daily activities occurred with adalimumab, infliximab, azathioprine (p < 0.001). Conclusion: Worries included having an ostomy bag, undergoing surgery, developing cancer: conditions significantly associated with worsened disease activity and low treatment adherence. Higher treatment adherence scores/greater workability improvements were observed in patients treated with anti-TNF-α agents.